2017
DOI: 10.1080/1351847x.2016.1274266
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying managerial overconfidence and corporate debt maturity structure

Abstract: We examine the impact of managerial overconfidence on corporate debt maturity. We build upon the argument that managerial overconfidence is likely to mitigate the underinvestment problem, which is often the major concern for long-term debt investors. Within this context, we hypothesise that managerial overconfidence increases debt maturity. Our empirical evidence, based on time-varying measures of overconfidence derived from computational linguistic analysis and directors' dealings in their own companies' shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…There is recent evidence on the mediating role of financial leverage [Detthamronga et al, 2017;Ramli et al, 2018;Naseem et al, 2020], but there is not enough empirical evidence that supports the mediating role of debt maturity except financial leverage [Hussain et al, 2020b]. By focusing on the mediating role of debt maturity on growth and insolvency risk relationship, some studies have established the relationship between board independence and debt maturity [Sheikh and Wang, 2012;Alves et al, 2015] and between CEO duality and debt maturity [Ataullah et al, 2018;Tosun and Senbet, 2020]. There is also plenty of evidence that supports the relationship between debt maturity and insolvency risk [Javadi and Mollagholamali, 2018;Brancati and Macchiavelli, 2020].…”
Section: Mediating Role Of Debt Maturitymentioning
confidence: 99%
“…There is recent evidence on the mediating role of financial leverage [Detthamronga et al, 2017;Ramli et al, 2018;Naseem et al, 2020], but there is not enough empirical evidence that supports the mediating role of debt maturity except financial leverage [Hussain et al, 2020b]. By focusing on the mediating role of debt maturity on growth and insolvency risk relationship, some studies have established the relationship between board independence and debt maturity [Sheikh and Wang, 2012;Alves et al, 2015] and between CEO duality and debt maturity [Ataullah et al, 2018;Tosun and Senbet, 2020]. There is also plenty of evidence that supports the relationship between debt maturity and insolvency risk [Javadi and Mollagholamali, 2018;Brancati and Macchiavelli, 2020].…”
Section: Mediating Role Of Debt Maturitymentioning
confidence: 99%
“…The conflict can also originate when the firm's capital structure has a risky debt inclusion to execute positive NPV (net present value) projects. These profits should be shared between bondholders and shareholders (Ataullah et al 2018;Khurana and Wang 2015). There are some other ways argued by (Myers 1977), that the maturity debt reduction also reduces the underinvestment problems despite having other means of conflict resolution e.g., including restrictive covenants to debt contracts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research design of many past studies relies on the firm's level measures such as growth opportunities, size, matching for the maturity of assets, interest ratio, firm's quality, liquidity etc. (Ataullah et al 2018;Dang and Phan 2016;Katper et al 2017). Moreover, some studies have been more focused on institutional or industrial classification, (Debortoli et al 2017;Fan et al 2012;Jõeveer 2013;Martins et al 2017;Naeem 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For these managers, short-term debt financing would optimize the allocation of cash flow. On the contrary, Ataullah, Vivian, & Xu (2012) reported that firms with chairman who have high level of self-attribution (SAB) and executive directors especially the CEOs who are overconfident, tend to have longer debt maturity, and make long-term borrowings. A recent study by Graham, Harvey, & Puri (2013) and Huang, Tan & Faff (2013) supported the earlier findings of Malmendier et al (2011) and (Landier & Thesmar, 2005, that is, overconfident managers tend to choose short term debt maturity.…”
Section: Literature Reviewsmentioning
confidence: 99%